Persepsi Peserta Didik Mengenai Penggunaan Smartphone sebagai Media Pembelajaran : Studi Deskriptif di SMP Negeri 236 Jakarta (International Forum of Researchers and Lecturers, 2025)
This study analyzes the perceptions of ninth-grade students at SMP Negeri 236 Jakarta regarding the use of smartphones as a learning medium in the 21st-century era, where digital technology advancements have transformed the educational landscape and made smartphones a relevant tool for learning. The research aims to identify student perceptions and the obstacles they face. Employing a quantitative descriptive method with questionnaires and interviews involving 139 respondents, findings reveal positive perceptions across cognitive (especially creativity), affective (comfort), and conative (active engagement) aspects. However, challenges such as rapid battery drain, internet data consumption, notification distractions, and misunderstandings with teachers persist. The implications of this research emphasize the need for regulations, guidance, and solutions to support responsible and effective smartphone use in learning.